Exploring Financial Stress: A Qualitative Study of Master`s Students Balancing Work and Postgraduate Studies - Venny Martha Elsya; Ulya Layyina; Dian Veronika Sakti Kaloeti (JURNAL BISNIS STRATEGI, 2025)
Objective: This qualitative research aims to provide deeper insight into master`s students who engage in dual roles as students and work simultaneously. It explored their financial stress based on the psychological and physiological responses to their financial condition.Methods: Interviews were conducted offline and online from various Indonesian universities in Semarang, Yogyakarta, Medan, Aceh, and Padang over the course of a month, each lasting approximately one hour. Participants' inclusion criteria were being a master's student in the current study, being employed, and being at least 21 years old. Following an intensive selection process, 9 students were chosen to take part. Transcripts were analysed using Atlas.ti 23 software through line-by-line open coding, following the principles of qualitative content analysis.Results: The five emerging subthemes provide financial stress responses for working master's students. The data reveal that the participants frequently experience anxiety and pressure due to insufficient income to cover basic necessities. The burden of such debt, identified as a significant source of stress, is worsened by an inability to set aside savings and a lack of financial literacy, which can lead to financial stress.Conclusion: The observed responses to financial stress in master’s students revealed important psychological and physiological indicators related to their financial status. It reveals a significant lack of financial literacy, which may serve as a proximal buffer to financial stress.